2021
DOI: 10.1016/j.dib.2021.107625
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data sets on the evaluation of graphene oxide as a thyroid endocrine disruptor and a modulator of gas gland cells in Japanese medaka (Oryzias latipes) larvae at the onset of maturity

Abstract: This article presents the experimental datasets obtained from the histological/histochemical studies of endocrine disrupting effects of graphene oxide (GO) on thyroid follicles and gas gland (GG) cells of Japanese medaka larvae at the onset of maturity. The experiment was conducted on one day-post hatch (dph) starved fries (orange-red variety) immersed in different concentrations of GO (2.5-20.0 mg/L) and no GO (controls) in embryo-rearing medium (ERM) for 96 h under laboratory conditions (25 ± 1 °C; light cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…From our histopathological evaluation of the gonadal structures and thyroid follicles, we found that the damages observed after GO administration was mainly due to aggregation/agglomeration of GO on or within the organs rather than directly acting as an EDC. 18,19,22,23 Our other investigation of GO effect on the sex reversal (SR) of medaka larvae showed no apparent EDC effect. 20,21 In the present study, we have extended our investigations on the histopathology of the IRG of medaka adults and larvae exposed to different concentrations/doses of GO either by a single intraperitoneal (IP) injection or by 96 h continuous immersion (IMR).…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…From our histopathological evaluation of the gonadal structures and thyroid follicles, we found that the damages observed after GO administration was mainly due to aggregation/agglomeration of GO on or within the organs rather than directly acting as an EDC. 18,19,22,23 Our other investigation of GO effect on the sex reversal (SR) of medaka larvae showed no apparent EDC effect. 20,21 In the present study, we have extended our investigations on the histopathology of the IRG of medaka adults and larvae exposed to different concentrations/doses of GO either by a single intraperitoneal (IP) injection or by 96 h continuous immersion (IMR).…”
mentioning
confidence: 79%
“…As the secondary sexual features were yet to develop in the larvae on 47th dph, the sex of the larvae was determined by phenotypic (histological examination of the gonads either as testis or ovary) and genotyping (XY and XX) methods. [20][21][22][23] We have observed that 27% male phenotypes instead of XY genotypes, were XX (8 XX larvae have testis out of 29 larvae with phenotypic testis), and we considered these larvae as sex-reversed during our previous studies on gonads 20,21 and thyroids. 22,23 In the present study, we are unable to track the IRG of all the experimental larvae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations